The Greed, Family, and the Supernatural: A Study of Di Ambang Kematian (2023) (Universitas Pamulang, 2024)
This study explores the complex relationship between family dynamics, supernatural beliefs, and the consequences of greed as depicted in the Indonesian horror film Di Ambang Kematian (2023). The film, directed by Azhar Kinoi Lubis, tells the tragic story of Nadia, who falls victim to her father's ritual search for wealth and reveals a moral stupidity driven by greed. The study investigated how a character's emotional response to loss and greed develops throughout the story using qualitative analysis and Elisabeth Kübler-Ross' five-stage grief theory. These results suggest that supernatural elements serve as metaphors for internal conflicts, illustrating the negative effects of materialism on family relationships. This study places Di Ambang Kematian as an important object about the dark aspects of human nature and cultural attitudes towards greed and helps to understand modern Indonesian horror cinema as a representation of fear and moral dilemma.